Stochastic wind-load model for building vibration estimation using large-eddy cfd simulation and random turbulenc flow generation algorithms - Inaudi, José A. (2017)
The application of computer fluid dynamics to the estimation of a stochastic wind loading model for vibration analysis of flexible buildings is studied in this paper. Large-Eddy-Simulation with random turbulence field as inflow boundary condition is used for estimating along the wind forces, across the wind forces and torsional moments along the height of the building. The stochastic turbulence of the inlet flow is modeled using techniques proposed in the literature and variations suggested by the authors, and along the wind and along the wind forces and torsional moments applied along the building height are estimated with sampled random processes resulting from the CFD analyses. The application of this numerical technique during the design stage of a concrete-wall 36-storey building with a parallelogram-shape plan is described. This structure is prone to high floor accelerations due to wind loading, compromising occupant comfort. The construction of random loading models for this building considering time and space correlation of forces and torsional moments is discussed and the use of the random loading to the design process of supplemental damping devices for the building is described.